2009
DOI: 10.1097/cmr.0b013e32831bc42f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of growth 4 is involved in melanomagenesis and induces growth suppression and apoptosis in melanoma cell line M14

Abstract: The objective of this study is as follows. Inhibitor of growth (ING) 4 is a novel member of the ING family. It has been thought to play an inhibitory role in several malignancies through its involvment in gene transcription, apoptosis, cell cycle control, and tumor angiogenesis. The involvement of ING4 in melanomagenesis remains unknown. The purpose of this study was to investigate the inhibitory effects of ING4 on melanoma and its mechanisms. The method used was to construct recombinant plasmid pcDNA3.1-ING4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
(35 reference statements)
3
38
0
Order By: Relevance
“…To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma. Similar to the results of previous studies regarding other malignant tumors (11,18,20,(28)(29)(30)(31), the results of the present study demonstrated that the osteosarcoma tissues had significantly decreased expression of ING4 when compared with the normal bone tissues (P<0.001). The majority of the osteosarcoma specimens had a score of (-) or (+), whilst no normal bone specimens had a score of (-) or (+).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma. Similar to the results of previous studies regarding other malignant tumors (11,18,20,(28)(29)(30)(31), the results of the present study demonstrated that the osteosarcoma tissues had significantly decreased expression of ING4 when compared with the normal bone tissues (P<0.001). The majority of the osteosarcoma specimens had a score of (-) or (+), whilst no normal bone specimens had a score of (-) or (+).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated that ING4 expression is suppressed or reduced in a number of malignancies, and the degree of expression is associated with the tumor grade (11,18,20,(28)(29)(30)(31). To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…[5][6][7][8] ING4 can significantly induce tumor growth suppression in different tumor types via induction of cell-cycle alteration and apoptosis and inhibition of tumor angiogenesis by repressing nuclear factor kB and hypoxia-inducible factor-1a activity and consequently reducing production of proangiogenic factors. 5,[9][10][11][12][13][14] ING4 can also enhance chemosensitivity to DNA-damage agents such as doxorubicin and etoposide in HepG2 hepatocarcinoma cells. 10 Furthermore, ING4 can exhibit remarkable inhibitory effect on tumor cell spreading, migration and invasion via colocalization and interaction with liprin a1 at lamellipodia 15 and downregulation of matrix metalloproteinase-2 and matrix metalloproteinase-9.…”
Section: Introductionmentioning
confidence: 99%